2011
DOI: 10.1007/s00421-011-1909-0
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac β-adrenergic responsiveness with exercise

Abstract: Left ventricular performance is enhanced with chronic exercise training. Alterations in cardiomyocyte β-adrenergic responsiveness (BAR) may, in part, mediate this response. In this study, cardiac BAR and the expression of some key cardiac hypertrophic signaling molecules following 3 months of treadmill training were examined. Four-month old, female, Wistar Kyoto (WKY) rats were randomly assigned into either a sedentary (WKY-SED, n = 15) or an exercise-trained (WKY-TRD, n = 11) group. All rats were maintained o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
(48 reference statements)
2
2
0
Order By: Relevance
“…Remarkably, acute NOS1 inhibition (+SMLT) normalized Ex myocyte contraction (Ca 2+ transients and cell shortening amplitude) and Ca 2+ decline to Sed myocyte levels (Fig 1D-F). In addition, Ex myocytes had a greater functional response (Ca 2+ transient and shortening amplitudes) to β-adrenergic receptor (β-AR) stimulation with isoproterenol (ISO) (Fig 1H), consistent with previous studies in animals and humans [34, 41, 53, 55]. As with basal contraction, acute NOS1 inhibition (+SMLT) abolished the increased functional response to low dose ISO in Ex myocytes.…”
Section: Resultssupporting
confidence: 89%
“…Remarkably, acute NOS1 inhibition (+SMLT) normalized Ex myocyte contraction (Ca 2+ transients and cell shortening amplitude) and Ca 2+ decline to Sed myocyte levels (Fig 1D-F). In addition, Ex myocytes had a greater functional response (Ca 2+ transient and shortening amplitudes) to β-adrenergic receptor (β-AR) stimulation with isoproterenol (ISO) (Fig 1H), consistent with previous studies in animals and humans [34, 41, 53, 55]. As with basal contraction, acute NOS1 inhibition (+SMLT) abolished the increased functional response to low dose ISO in Ex myocytes.…”
Section: Resultssupporting
confidence: 89%
“…Therefore, we tested the myocardial ANP and BNP mRNA and found that the ANP mRNA in the ME group was significantly increased, and that ANP mRNA levels in rats from group E tended to increase, but with was no changes in BNP mRNA levels. The Libonati team conducted a 12-week treadmill exercise intervention on Wistar rats and reported no changes in ANP mRNA in the exercise and the sedentary groups 42 , which is consistent with the results of our study. In addition, BNP levels did not change significantly in exercised rats 43 , similar to the results of our study as well.…”
Section: Discussionsupporting
confidence: 91%
“…An increased responsiveness to isoproterenol has been demonstrated in the myocardium of trained rodents, when compared with sedentary controls (Takeda et al, 1985; Libonati and MacDonnell, 2011). Such responses have been shown to be independent of training-induced alterations in cardiac hypertrophy or hypertrophic marker expression.…”
Section: Aging Physical Exercise and Beta Adrenergic System: The Momentioning
confidence: 99%